A Color Image Encryption Scheme Based on a Novel 3D Chaotic Mapping. (23rd December 2020) - Liu, Chunyuan; Ding, Qun
Abstract : Low-dimensional chaotic mappings are simple functions that have low computation cost and are easy to realize, but applying them in a cryptographic algorithm will lead to security vulnerabilities. To overcome this shortcoming, this paper proposes the coupled chaotic system, which coupled the piecewise and Henon mapping. Simulation results indicate that the novel mapping has better complexity and initial sensitivity and larger key space compared with the original mapping. Then, a new color image encryption algorithm is proposed based on the new chaotic mapping. The algorithm has two processes: diffusion and confusion. In this scheme, the key is more than 2 216, and SSIM and PSNR are 0.009675 and 8.6767, respectively. The secret key is applied in the shuffling and diffusion. Security analysis indicates that the proposed scheme can resist cryptanalytic attacks. It has superior performance and has high security.